FERULA L. ТУЎЫСЫ ТҮРЛЕРИНИҢ ТИРИШИЛИК ФОРМАЛАРЫНЫҢ ЖАСАЎ ШАРАЯТЫНА БАЙЛАНЫСЛЫ ҚӘЛИПЛЕСИЎИ - Темирбеков, О.; Каниязов, А.; Дильманова, А. (FAN va JAMIYAT, 2016)
The article deals with the issues of influence of changing conditions of life on formation of existence forms of the biggest, relative Ferula L.,relating to the family of umbellate.